Who cares about sustainability and why?: motivations to care about ethical labels on coffee from the perspectives of consumers, industry professionals and Honduran smallholder coffee growers - Szalai, Krisztina (2017)
Certification schemes have become widely adopted across the coffee industry and are thought to act as a mechanism for reducing poverty, conservation of environmental assets and well-being of agricultural producers and workers. These sustainability credentials also allow retailers and manufacturers to use certifications to differentiate themselves in a crowded marketplace. My research focused on understanding the perceived value of voluntary certification standards in the coffee sector, with particular emphasis on the motivations of key stakeholders to care about social and environmental challenges within the coffee supply chain. By investigating the extent to which certification standards are capable of bridging the geographic and information gap between production and consumption of an agricultural commodity, this research investigates relating to moral motivations of caring-at-a-distance, and highlights limitations of voluntary certification standards to eradicate poverty and achieve large-scale conservation in smallholder-dominated coffee-production landscapes.